EVALUASI PROSES PENGAJUAN LAPORAN PERKEMBANGAN STUDI PADA LAMAN BEASISWA KEMENDIKTISAINTEK ASRAMA MAHASISWA NUSANTARA (AMN) SURABAYA - Alin Kania P. Raweyai; Lorna Stevani Amoye; Stenly P. R. Ansanay; Evi Silvia Melina (JOSH: Journal of Sharia, 2026)
This study aims to evaluate the process of submitting the Study Progress Report (Laporan Perkembangan Studi/LPS) through the Kemendiktisaintek scholarship platform at Asrama Mahasiswa Nusantara (AMN) Surabaya in order to identify supporting factors, implementation barriers, and the effectiveness of the process. The research employed a qualitative descriptive-evaluative approach using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews, observations, and documentation involving scholarship recipients, administrative staff, and AMN management. The findings indicate that, in the context dimension, the objectives and policies of LPS reporting were well understood by stakeholders as a mechanism for academic monitoring and a prerequisite for scholarship fund disbursement. In the input dimension, adequate internet facilities and a multi-layered mentoring system involving mentors, dormitory leaders, and administrative staff were available, although the utilization of digital guidelines remained limited. In the process dimension, several obstacles were identified, including CAPTCHA errors during login, lengthy re-verification procedures for revised documents, and difficulties in obtaining academic documents from students’ respective universities. In the product dimension, the system was found to support administrative discipline and academic progress monitoring, although its effectiveness was still affected by technical and procedural constraints. This study demonstrates that the success of digital scholarship services is determined not only by the quality of the information system but also by institutional support mechanisms and the efficiency of administrative procedures. The findings contribute to the development of digital public service evaluation, particularly in the context of higher education scholarship management. Based on the results, improvements are recommended in the CAPTCHA feature, the acceleration of revised document verification procedures, and the enhancement of socialization efforts regarding digital guidelines and complaint-handling services for students.